Novel supported catalyst, preparation method thereof and method for preparing 2, 2-dimethyl-1, 3-dioxolane

By loading bismuth phosphotungstate on the chlorite mesoporous composite material, a new type of supported catalyst was prepared, which solved the problems of poor catalyst efficiency and low target product yield in the prior art, and achieved efficient production of 2,2-dimethyl-1,3-dioxolane.

CN119793533AActive Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311308577.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

In the prior art, there is a problem that the catalyst efficiency is poor and the target product yield is low in the production process of 2,2-dimethyl-1,3-dioxolane.

Method used

A new type of supported catalyst was prepared by using chlorite mesoporous composite material as a support, and acetone and ethylene glycol were condensed in the presence of a catalyst and aqueous agent.

Benefits of technology

The yield of 2,2-dimethyl-1,3-dioxolane is improved. The support and active components of the catalyst are both inorganic materials, with stable properties, high temperature resistance, no swelling during the reaction process, mild process conditions, and low requirements for the reaction device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793533A_ABST
    Figure CN119793533A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fine chemical engineering, and discloses a novel supported catalyst, a preparation method thereof and a method for preparing 2, 2-dimethyl-1, 3-dioxolane. The novel supported catalyst comprises a chlorite mesoporous composite material and bismuth phosphotungstate supported on the chlorite mesoporous composite material. The average particle size of the chlorite mesoporous composite material is 10-60 [mu] m, the specific surface area is 200-600 m < 2 > / g, the pore volume is 0.8-2 mL / g, the pore diameter is in bimodal distribution, and the first most probable pore diameter and the second most probable pore diameter corresponding to double peaks are 3-6 nm and 18-22 nm respectively; on the basis of the total weight of the catalyst, the content of the chlorite mesoporous composite material is 55-85 wt%, and the content of the bismuth phosphotungstate is 15-45 wt%. The catalyst is used for condensation reaction of acetone and ethylene glycol, and higher 2, 2-dimethyl-1, 3-dioxolane yield can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fine chemicals, and in particular to a novel supported catalyst and a preparation method thereof, and a method for preparing 2,2-dimethyl-1,3-dioxolane. Background Art

[0002] Ketal (aldehyde) is an important type of carbonyl condensation compound, which is the product of the condensation of carbonyl compounds and diols under acidic conditions. It is usually used in the synthesis of steroids and sugars, carbonyl protection of organic compounds, paints, and as an intermediate and target product in the pharmaceutical industry; because ketal compounds have floral, fruity or special aromas, and have long-lasting fragrance and stable chemical properties, they are also often used in spices, such as flavoring and fixing of alcoholic beverages, soft drinks, ice cream, cosmetics, etc.; at the same time, ketal spices can also be used to prepare edible flavors such as chicken flavor, meat flavor, and cream. Therefore, ketal has great market development potential and has attracted the attention of many researchers. Among them, 2,2-dimethyl-1,3-dioxolane is an important intermediate in the new process of petrochemical product ethylene glycol. The 1,3-dioxolane compounds can be used as solvents in industry to replace commonly used industrial solvents such as dichloromethane, dichloroethane and butanone, and can also be used as solvents for polymers (Kirk-Othmer Encydopedia of Chemical Technology, John Wllley, Sons, Now Pork, Vol. 12: page 710).

[0003] There are many methods for synthesizing ketals, among which the most commonly used is to condense ketone compounds with alcohol compounds in the presence of a catalyst. In the prior art, when preparing 2,2-dimethyl-1,3-dioxolane, the catalyst used is mainly a protonic acid catalyst (including inorganic acid and organic acid) or a Lewis acid catalyst. When acid catalysts catalyze cyclization reactions, they have the disadvantages of easy corrosion of equipment, large dosage, difficult separation of products, low product selectivity, and easy environmental pollution. Therefore, it is still of positive significance to seek ketal catalysts that have strong catalytic activity, high selectivity, and are easy to separate from the reaction system. Ketal catalysts for multiphase reactions are currently a relatively active research field. At present, the catalysts that have been reported to replace concentrated sulfuric acid include strong acid ion exchange resins, heteropoly acids, ionic liquids, solid superacids, etc., and have achieved good results. Among them, strong acid ion exchange resins have attracted widespread attention due to their advantages such as insolubility in the reaction system, good stability, high selectivity, low cost, and easy separation. Strong acid ion exchange resin is a polymer material containing acidic functional active ingredients, which has strong catalytic ability for esterification, aldehyde-ketone condensation, etherification, etc. However, the acid strength of strong acid cation exchange resin acid is weaker than that of sulfuric acid. When used alone as a ketal catalyst, the reaction rate is slower than that of concentrated sulfuric acid. For researchers, developing excellent ketal catalysts, improving reaction efficiency, and inhibiting the formation of by-products are important future work directions. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of poor catalyst efficiency and low target product yield in the production process of 2,2-dimethyl-1,3-dioxolane in the prior art, and to provide a novel supported catalyst and a preparation method thereof, as well as a method for preparing 2,2-dimethyl-1,3-dioxolane. The catalyst is used for the condensation reaction of acetone and ethylene glycol, and a higher yield of 2,2-dimethyl-1,3-dioxolane can be obtained.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a novel supported catalyst, wherein the novel supported catalyst comprises a chlorite mesoporous composite material and bismuth phosphotungstate supported on the chlorite mesoporous composite material; wherein the average particle size of the chlorite mesoporous composite material is 10-60 μm, and the specific surface area is 200-600 m 2 / g, the pore volume is 0.8-2mL / g, and the pore size is bimodal distribution; wherein the first most probable pore size and the second most probable pore size corresponding to the bimodal distribution are 3-6nm and 18-22nm, respectively; and based on the total weight of the catalyst, the content of the chlorite mesoporous composite material is 55-85% by weight, and the content of the bismuth phosphotungstate is 15-45% by weight.

[0006] The second aspect of the present invention provides a method for preparing the aforementioned novel supported catalyst, wherein the preparation method comprises:

[0007] The bismuth trichloride solution is dropped into a mixed solution of a chlorite mesoporous composite material and a phosphotungstic acid solution to carry out a contact reaction, and the solvent is removed after the reaction to obtain a solid product; the solid product is dried and calcined to obtain a novel supported catalyst.

[0008] The third aspect of the present invention provides a method for preparing 2,2-dimethyl-1,3-dioxolane, wherein the method comprises: in the presence of a catalyst and a water-carrying agent, contacting acetone and ethylene glycol to carry out a condensation reaction, wherein the catalyst is the novel supported catalyst described above.

[0009] Through the above technical solution, the technical solution of the present invention has the following advantages:

[0010] 1. The carrier and active components of the novel supported catalyst provided by the present invention are all inorganic materials, which are stable in nature, have good high temperature resistance, and do not swell during the reaction.

[0011] 2. The raw materials of the novel supported catalyst provided by the present invention are easily available, the preparation method is simple, the conditions are easy to control, and the product has good reproducibility.

[0012] 3. When the novel supported catalyst provided by the present invention is used to synthesize 2,2-dimethyl-1,3-dioxolane, the process conditions are mild and the requirements for the reaction device are not high.

[0013] 4. When the new supported catalyst provided by the present invention is used to synthesize 2,2-dimethyl-1,3-dioxolane, the yield of the target product is high.

[0014] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the XRD spectrum of the chlorite mesoporous composite material A prepared in Example 1;

[0016] Figure 2 is a SEM scanning electron microscope image of the chlorite mesoporous composite material A prepared in Example 1;

[0017] Figure 3 is the pore size distribution curve of the chlorite mesoporous composite material A prepared in Example 1. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] As mentioned above, the first aspect of the present invention provides a novel supported catalyst, wherein the novel supported catalyst comprises a chlorite mesoporous composite material and bismuth phosphotungstate supported on the chlorite mesoporous composite material; wherein the average particle size of the chlorite mesoporous composite material is 10-60 μm, and the specific surface area is 200-600 m 2 / g, the pore volume is 0.8-2mL / g, and the pore size is bimodal distribution; wherein the first most probable pore size and the second most probable pore size corresponding to the bimodal distribution are 3-6nm and 18-22nm, respectively; and based on the total weight of the catalyst, the content of the chlorite mesoporous composite material is 55-85% by weight, and the content of the bismuth phosphotungstate is 15-45% by weight.

[0020] The inventors of the present invention have found that: in the prior art, the catalysts used for ketone-alcohol condensation reactions are divided into two categories: homogeneous and heterogeneous. Among them, homogeneous catalysts mainly include inorganic acid solutions and organic acids, and heterogeneous catalysts mainly include solid acid catalysts and supported catalysts. The advantages of homogeneous catalysts are low price and good catalytic activity, but they are gradually eliminated due to defects such as difficulty in separating products from catalysts, more side reactions, and easy corrosion of equipment. Although heterogeneous catalysts solve the problems of difficult product separation and serious equipment corrosion, they are rarely used in industrial production due to shortcomings such as poor catalytic stability and low product yield. Developing a new solid catalyst system to make up for the performance defects of the above-mentioned catalysts is a good way to solve the problem.

[0021] Heteropolyacids with Keggin structures such as phosphotungstic acid, silicotungstic acid, and phosphomolybdic acid are good condensation catalysts, but these catalysts are easily soluble in water and organic solvents and are not suitable for most organic reactions. The corresponding heteropolyacid salts (e.g., bismuth phosphotungstate) not only maintain good catalytic performance, but are also not easily soluble in water and organic solvents, and are good heterogeneous condensation catalysts. However, bismuth phosphotungstate is not suitable for fixed bed reactors because it is not easy to shape. Therefore, a suitable carrier is selected to load bismuth phosphotungstate to prepare a new catalyst, which can be used for ketone-alcohol condensation reaction. In order to make bismuth phosphotungstate evenly dispersed, it is necessary to select a carrier with a special structure. The chlorite mesoporous composite material combines the advantages of a mesoporous molecular sieve material with a three-dimensional cubic pore structure, a mesoporous molecular sieve material with a hexagonal pore structure, and chlorite, and is very suitable for use as a carrier for a supported catalyst.

[0022] The inventors of the present invention found in the process of developing ketone-alcohol condensation catalysts that if bismuth phosphotungstate is loaded on a chlorite mesoporous composite material, an organic condensation reaction catalyst with excellent performance can be prepared. The catalyst can show good catalytic activity and target product yield when used in the synthesis reaction of 2,2-dimethyl-1,3-dioxolane.

[0023] According to the present invention, preferably, based on the total weight of the catalyst, the content of the chlorite mesoporous composite material is 60-80% by weight, and the content of the bismuth phosphotungstate is 20-40% by weight; more preferably, based on the total weight of the catalyst, the content of the chlorite mesoporous composite material is 65-75% by weight, and the content of the bismuth phosphotungstate is 25-35% by weight. In the present invention, if the new supported catalyst has the aforementioned specific content of the chlorite mesoporous composite material and the content of bismuth phosphotungstate, the prepared catalyst can have better catalytic activity and target product yield when used for ketone-alcohol condensation reaction.

[0024] According to the present invention, preferably, the specific surface area of ​​the chlorite mesoporous composite material is 228-349m 2 / g, pore volume is 1.2-1.7mL / g, the first most probable pore size and the second most probable pore size are 3.6-4.2nm and 19-21nm respectively. In the present invention, the chlorite mesoporous composite material with the aforementioned specific structural parameters can make full use of the structural advantages of the chlorite mesoporous composite material to achieve uniform dispersion of bismuth phosphotungstate active sites.

[0025] According to the present invention, the specific surface area of ​​the novel supported catalyst is 100-350m 2 / g, pore volume 0.6-1.5cm 3 / g; preferably, the specific surface area of ​​the novel supported catalyst is 150-300m 2 / g, pore volume is 0.8-1.4cm 3 / g; More preferably, the specific surface area of ​​the novel supported catalyst is 180-270m 2 / g, pore volume is 1-1.3cm 3 In the present invention, the novel supported catalyst having the aforementioned specific parameters is used, so that the catalyst has better catalytic activity and target product yield when used in ketone-alcohol condensation reaction.

[0026] According to the present invention, the chlorite mesoporous composite material can be synthesized according to the following method:

[0027] (a) in the presence of a template and butanol, tetraethyl orthosilicate is contacted with an acid agent, and the resulting mixture is crystallized and filtered to obtain a mesoporous molecular sieve material filter cake 1 having a three-dimensional cubic pore structure;

[0028] (b) contacting and reacting ethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia, and crystallizing and filtering the mixture obtained after the contact reaction to obtain a mesoporous molecular sieve material filter cake 2 having a hexagonal pore structure;

[0029] (c) mixing the mesoporous molecular sieve material filter cake 1, the mesoporous molecular sieve material filter cake 2, silica gel and chlorite and ball-milling them, slurrying the solid powder obtained after ball milling with water, spray-drying the obtained slurry, and then removing the template in the obtained product.

[0030] In step (a), the molar ratio of the template, butanol and tetraethyl orthosilicate can be 1:10-100:10-90, preferably 1:60-90:50-75.

[0031] In step (a), the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene; most preferably, the template has a molecular formula of EO 20 PO 70 EO 20 The template agent can be purchased commercially (for example, it can be purchased from Aldrich Company with the trade name P123).

[0032] In step (a), the acidic agent can be various conventional substances or mixtures (such as solutions) that can be used to adjust the pH value. Preferably, the acidic agent is hydrochloric acid. The hydrochloric acid as an acidic agent is preferably used in the form of an aqueous solution. The pH value of the hydrochloric acid aqueous solution can be 1-6.

[0033] In step (a), the butanol is preferably n-butanol.

[0034] In step (a), the conditions for contacting the tetraethyl orthosilicate with the acid agent may include: temperature of 10-60° C., time of 10-72 hours, and pH of 1-7. In order to facilitate uniform mixing of the substances, the contacting of the tetraethyl orthosilicate with the acid agent is preferably carried out under stirring conditions.

[0035] In step (a), the crystallization conditions may include: a temperature of 30-150° C. and a time of 10-72 hours. Preferably, the crystallization conditions include: a temperature of 40-100° C. and a time of 20-40 hours. The crystallization is performed by a hydrothermal crystallization method.

[0036] In step (b), the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide (CTAB) and ammonia may be 1:0.1-1:0.1-5, preferably 1:0.2-0.5:1.5-3.5.

[0037] In step (b), the ammonia is preferably added in the form of aqueous ammonia.

[0038] In step (b), the contact reaction process of ethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia is carried out in the presence of water. Preferably, part of the water is introduced in the form of ammonia water, and part of the water is added in the form of deionized water. In the contact reaction system of ethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia, the molar ratio of ethyl orthosilicate to water can be 1:100-200, preferably 1:120-180.

[0039] In step (b), the conditions for the contact reaction of ethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia may include: a temperature of 25-100° C. and a time of 10-72 hours. Preferably, the contact reaction is carried out under stirring to facilitate uniform mixing of the substances.

[0040] In step (b), the crystallization conditions may include: a temperature of 30-150° C. and a time of 10-72 hours. Preferably, the crystallization conditions include: a temperature of 40-100° C. and a time of 20-40 hours. The crystallization is performed by a hydrothermal crystallization method.

[0041] In step (c), relative to 100 parts by weight of the mesoporous molecular sieve material filter cake 1, the amount of the mesoporous molecular sieve material filter cake 2 is preferably 50-200 parts by weight; the amount of the silica gel is preferably 100-300 parts by weight; the amount of the chlorite is preferably 40-100 parts by weight.

[0042] In step (c), the ball milling can be carried out in a ball mill, the inner wall of the ball milling jar in the ball mill is preferably lined with polytetrafluoroethylene, and the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball milling jar, and for a ball milling jar of 50-150 ml, 1-2 grinding balls can usually be used; the material of the grinding balls can be agate, polytetrafluoroethylene, etc., preferably agate. The conditions for the ball milling can include: the rotation speed of the grinding balls can be 300-500r / min, the temperature in the ball milling jar can be 15-100°C, and the ball milling time can be 0.1-100 hours.

[0043] In step (c), the solid powder is slurried with water at 25-60° C. In the slurrying process, the weight ratio of the solid powder to water can be 1:0.1-2, preferably 1:0.3-0.9.

[0044] In step (c), the spray drying can be carried out in a conventional manner, for example, in an atomizer. The spray drying conditions may include: a temperature of 100-300°C, and a rotation speed of 10000-15000 r / min; preferably, the spray drying conditions include: a temperature of 150-250°C, and a rotation speed of 11000-13000 r / min.

[0045] In step (c), the conditions for removing the template may include: a temperature of 300-600° C. and a time of 10-80 hours.

[0046] The second aspect of the present invention provides a method for preparing the aforementioned novel supported catalyst, wherein the preparation method comprises:

[0047] The bismuth trichloride solution is added dropwise to a mixed solution of a chlorite mesoporous composite material and a phosphotungstic acid solution to react, and the solvent after the reaction is removed to obtain a solid product; the solid product is dried and calcined to obtain a novel supported catalyst.

[0048] According to the present invention, the bismuth trichloride solution is a bismuth trichloride aqueous solution or a bismuth trichloride ethanol solution; the concentration of the bismuth trichloride solution can be 1-30% by weight, preferably 5-20% by weight.

[0049] According to the present invention, the phosphotungstic acid solution is a phosphotungstic acid aqueous solution or a phosphotungstic acid ethanol solution; the concentration of the phosphotungstic acid solution may be 2-50% by weight, preferably 10-30% by weight.

[0050] According to the present invention, the weight ratio of the chlorite mesoporous composite material, the phosphotungstic acid solution and the bismuth trichloride solution is 1:(1-8):(0.1-2), preferably 1:(1.5-4):(0.1-1.2).

[0051] According to the present invention, the reaction conditions include: a reaction temperature of 10-80°C, preferably 20-60°C; a reaction time of 1-30h, preferably 3-8h; preferably, in order to achieve a better mixing effect, rapid stirring or ultrasonic means can be used to improve the reaction efficiency during the contact reaction of the chlorite mesoporous composite material, phosphotungstic acid and bismuth trichloride solution.

[0052] According to the present invention, there is no particular requirement for the method of removing the solvent, and it can be a method known in the art, for example, using a rotary evaporator or heating and evaporating the solvent during stirring.

[0053] According to the present invention, the drying conditions include: the temperature can be 60-150° C., preferably 80-120° C.; the time is 2-20 hours, preferably 3-12 hours.

[0054] According to the present invention, the calcination conditions include: a temperature of 200-400° C., preferably 250-300° C.; and a calcination time of 1-10 h, preferably 3-6 h.

[0055] The third aspect of the present invention provides a method for preparing 2,2-dimethyl-1,3-dioxolane, wherein the method comprises: in the presence of a catalyst and a water-carrying agent, contacting acetone with ethylene glycol for a condensation reaction, wherein the catalyst is the novel supported catalyst described above.

[0056] According to the present invention, the water-carrying agent is cyclohexane or benzene.

[0057] According to the present invention, the weight ratio of the novel supported catalyst, the water-carrying agent, acetone and ethylene glycol is 1: (8-50): (10-60): (20-100).

[0058] According to the present invention, the conditions of the condensation reaction include: temperature of 60-100° C., preferably 70-90° C.; time of 0.5-10 h, preferably 1-6 h.

[0059] The present invention will be described in detail below through examples.

[0060] In the following examples and comparative examples:

[0061] The small-angle XRD test of the sample was carried out on a D8 ADVANCE high-power rotating target X-ray diffractometer produced by BRUKER AXS of Germany, with a scanning range of 0.5-10°.

[0062] The scanning electron microscope images of the samples were obtained using an XL-30 field emission environmental scanning electron microscope produced by FEI Company in the United States.

[0063] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0064] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 350°C for 4 hours before measurement, and the specific surface area of ​​the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.

[0065] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0066] The template agent P123 used in the examples and comparative examples was purchased from Aldrich Company; the other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd., and the purity of the reagents was analytical grade.

[0067] Example 1

[0068] (1) Preparation of spherical chlorite mesoporous composite materials

[0069] 60 g (0.001 mol) of triblock copolymer surfactant P123 was dissolved in 100 ml of hydrochloric acid aqueous solution (pH 4) and 2000 g of deionized water solution, and stirred for 4 h until P123 was dissolved to form a transparent solution. 60 g (0.8 mol) of n-butanol was added to the transparent solution and stirred for 1 h. The solution was then placed in a 40°C water bath, and 129 g (0.62) of ethyl orthosilicate was slowly added dropwise to the solution. The solution was stirred for 24 h while maintaining the temperature at about 40°C and pH 4.5. The solution was then hydrothermally treated at 100°C for 24 h, filtered and washed with deionized water for 4 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 1 having three-dimensional cubic pores.

[0070] Hexadecyltrimethylammonium bromide and tetraethyl orthosilicate are added to an ammonia solution with a concentration of 25 wt %, wherein the amount of tetraethyl orthosilicate added is 208 g, and the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, and ammonia to water in the ammonia solution is 1:0.4:2.5:150, and stirred at 50°C for 24 hours, and then hydrothermally treated at 80°C for 30 hours, followed by filtration and washing with deionized water for 4 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 2 with a hexagonal pore structure.

[0071] Put 10g of the prepared mesoporous molecular sieve material cake 1, 10g of the mesoporous molecular sieve material cake 2, 20g of silica gel and 7g of chlorite into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 400r / min. Close the ball mill, and mill at a temperature of 60°C in the ball mill for 1 hour to obtain a solid powder; dissolve the solid powder in 50ml of deionized water, spray dry at 200°C and a rotation speed of 12000r / min; calcine the product obtained after spray drying at 500°C in a muffle furnace for 30 hours to remove the template agent to obtain a chlorite mesoporous composite material A.

[0072] The specific surface area of ​​chlorite mesoporous composite material A is 320 m 2 / g, and the pore volume is 1.6ml / g.

[0073] Figure 1 is the XRD spectrum of chlorite mesoporous composite material A. Figure 1 It can be seen from the small-angle spectral peaks appearing in the chlorite mesoporous composite material A that it has an ordered three-dimensional cubic pore structure and a hexagonal pore structure.

[0074] Figure 2 This is the SEM image of the chlorite mesoporous composite material A. Figure 2 It can be seen that the microscopic morphology of the chlorite mesoporous composite material A is mesoporous spheres with a particle diameter of 10-60 μm.

[0075] Figure 3 is the pore size distribution curve of the chlorite mesoporous composite material A. It can be seen that the chlorite mesoporous composite material A has an obvious dual pore distribution structure, the first most probable pore size is 4 nm, and the second most probable pore size is 20 nm.

[0076] (2) Preparation of new supported catalysts

[0077] 100g of chlorite mesoporous composite material A and 200g of phosphotungstic acid aqueous solution with a mass concentration of 20% were mixed and stirred at 60°C for 1h; 44g of bismuth trichloride aqueous solution with a mass concentration of 10% was slowly added to the above mixture; after the addition was completed, it was stirred at 60°C for 4h. The solvent water in the system was removed by a rotary evaporator, the solid product was dried at 100°C for 8h, and then calcined at 280°C for 4h to obtain a new supported catalyst A.

[0078] Based on the total weight of the catalyst A, the content of the chlorite mesoporous composite material A was 69.8% by weight, and the content of bismuth phosphotungstate was 30.2% by weight.

[0079] The specific surface area of ​​catalyst A is 228m 2 / g, and the pore volume is 1.2ml / g.

[0080] (3) Catalyst reaction performance evaluation

[0081] Add 11.6g acetone and 18.6g ethylene glycol, 10g cyclohexane with water and 0.5g new supported catalyst A to a 100ml three-necked flask, and install a thermometer, a water separator and a reflux condenser. Heat and reflux until almost no water is separated. After the reaction is completed, the reaction system is cooled to room temperature and the water layer is released. Filter the reaction solution, recover the catalyst, wash the filtrate with saturated brine and distilled water in turn, combine the organic layers, dry with anhydrous magnesium sulfate, first distill and recover cyclohexane (boiling point 80-81°C), then distill and collect the product 2,2-dimethyl-1,3-dioxolane (boiling point 92-93°C), weigh and calculate the yield. The yield of 2,2-dimethyl-1,3-dioxolane is 96.8%.

[0082] Example 2

[0083] (1) Preparation of spherical chlorite mesoporous composite materials

[0084] 60 g (0.001 mol) of triblock copolymer surfactant P123 was dissolved in 80 ml of hydrochloric acid aqueous solution (pH 5) and 1500 g of deionized water solution, and stirred for 4 h until P123 was dissolved to form a transparent solution. 23 g (0.3 mol) of n-butanol was added to the transparent solution and stirred for 1 h. 50 g (0.24) of ethyl orthosilicate was slowly added dropwise to the solution at 10 °C, and stirred for 24 h while maintaining the temperature at 10 °C and pH 6.1. The solution was then hydrothermally treated at 40 °C for 40 h, filtered and washed with deionized water for 4 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 1 having three-dimensional cubic pores.

[0085] Hexadecyltrimethylammonium bromide and tetraethyl orthosilicate are added to an ammonia solution with a concentration of 25 wt %, wherein the amount of tetraethyl orthosilicate added is 208 g, and the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, and ammonia to water in the ammonia solution is 1:0.2:1.5:120, and stirred at 25°C for 24 hours, and then hydrothermally treated at 40°C for 40 hours, followed by filtration and washing with deionized water for 4 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 2 with a hexagonal pore structure.

[0086] Put 10g of the prepared mesoporous molecular sieve material cake 1, 5g of the mesoporous molecular sieve material cake 2, 30g of silica gel and 4g of chlorite into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 2mm, the number is 2, and the rotation speed is 300r / min. Close the ball mill, and mill for 0.5 hours at a temperature of 80°C in the ball mill to obtain a solid powder; dissolve the solid powder in 50ml of deionized water, spray dry at 150°C and a rotation speed of 13000r / min; calcine the product obtained after spray drying at 300°C in a muffle furnace for 80 hours to remove the template agent to obtain a chlorite mesoporous composite material B.

[0087] The specific surface area of ​​chlorite mesoporous composite material B is 301m 2 / g, the pore volume is 1.5ml / g, the first most probable pore diameter is 3.6nm, and the second most probable pore diameter is 21nm.

[0088] (2) Preparation of new supported catalysts

[0089] 100g of chlorite mesoporous composite material B was mixed with 170g of 30% phosphotungstic acid ethanol solution, stirred at 25°C for 1h to completely dissolve it; 112g of 5% bismuth trichloride ethanol solution was slowly added to the mixture; after the addition was completed, it was stirred at 25°C for 8h. After the reaction was completed, stirring was stopped, and the solvent ethanol was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 80°C for 12h and calcined at 250°C for 6h to obtain a new supported catalyst B.

[0090] Based on the total weight of the catalyst B, the content of the chlorite mesoporous composite material B is 65% by weight, and the content of bismuth phosphotungstate is 35% by weight.

[0091] The specific surface area of ​​catalyst B is 180 m 2 / g, and the pore volume is 1ml / g.

[0092] The ketal reaction performance of catalyst B was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 96.3%.

[0093] Example 3

[0094] (1) Preparation of spherical chlorite mesoporous composite materials

[0095] 60 g (0.001 mol) of triblock copolymer surfactant P123 was dissolved in 200 ml of hydrochloric acid aqueous solution (pH 3) and 3000 g of deionized water solution, and stirred for 4 h until P123 was dissolved to form a transparent solution. 75 g (1 mol) of n-butanol was added to the transparent solution and stirred for 1 h. 180 g (0.86) of ethyl orthosilicate was slowly added dropwise to the solution in a 60°C water bath. The solution was stirred for 24 h while maintaining the temperature at 60°C and pH 3.8. The solution was then hydrothermally treated at 60°C for 32 h. The solution was then filtered and washed with deionized water for 4 times. The filter cake 1 of the mesoporous molecular sieve material having three-dimensional cubic pores was obtained by suction filtration.

[0096] Hexadecyltrimethylammonium bromide and tetraethyl orthosilicate are added to an ammonia solution with a concentration of 25 wt %, wherein the amount of tetraethyl orthosilicate added is 208 g, and the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, and ammonia to water in the ammonia solution is 1:0.5:3.5:180, and stirred at 100° C. for 4 hours, and then hydrothermally treated at 100° C. for 20 hours, followed by filtering and washing with deionized water for 4 times, and then suction filtration to obtain a mesoporous molecular sieve material filter cake 2 with a hexagonal pore structure.

[0097] Put 10g of the prepared mesoporous molecular sieve material cake 1, 20g of the mesoporous molecular sieve material cake 2, 10g of silica gel and 10g of chlorite into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 500r / min. Close the ball mill, and mill the ball at a temperature of 40°C for 4 hours to obtain a solid powder; dissolve the solid powder in 50ml of deionized water, spray dry at 250°C and a rotation speed of 11000r / min; calcine the product obtained after spray drying at 600°C in a muffle furnace for 10 hours to remove the template agent to obtain a chlorite mesoporous composite material C.

[0098] The specific surface area of ​​chlorite mesoporous composite material C is 349 m 2 / g, the pore volume is 1.7ml / g, the first most probable pore diameter is 4.2nm, and the second most probable pore diameter is 19nm.

[0099] (2) Preparation of new supported catalysts

[0100] 100g of chlorite mesoporous composite material C and 310g of 10% phosphotungstic acid aqueous solution were mixed and stirred at 40°C for 1h to completely dissolve; 23g of 15% bismuth trichloride aqueous solution was slowly added to the mixture; after the addition was completed, the mixture was stirred at 40°C for 5h. After the reaction was completed, stirring was stopped and the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 120°C for 3h and calcined at 300°C for 3h to obtain a new supported catalyst C.

[0101] Based on the total weight of the catalyst C, the content of the chlorite mesoporous composite material C is 75 weight %, and the content of bismuth phosphotungstate is 25 weight %.

[0102] The specific surface area of ​​catalyst C is 270 m 2 / g, and the pore volume is 1.3ml / g.

[0103] The ketal reaction performance of catalyst C was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 96.1%.

[0104] Example 4

[0105] Catalyst D was prepared in the same manner as in Example 1, except that the preparation conditions of the novel supported catalyst in step (2) of Example 1 were changed, specifically:

[0106] 100g of chlorite mesoporous composite material A and 311g of 20% phosphotungstic acid aqueous solution were mixed and stirred at 60°C for 1h; 68g of 10% bismuth trichloride aqueous solution was slowly added to the mixture; after the addition was completed, the mixture was stirred at 60°C for 4h. The solvent water in the system was removed by a rotary evaporator, the solid product was dried at 100°C for 8h, and then calcined at 280°C for 4h to obtain a new supported catalyst D.

[0107] Based on the total weight of the catalyst D, the content of the chlorite mesoporous composite material A is 60 weight %, and the content of bismuth phosphotungstate is 40 weight %.

[0108] The specific surface area of ​​catalyst D is 150 m 2 / g, and the pore volume is 0.8ml / g.

[0109] The ketal reaction performance of catalyst D was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 94.7%.

[0110] Example 5

[0111] Catalyst E was prepared in the same manner as in Example 3, except that the preparation conditions of the novel supported catalyst in step (2) of Example 3 were changed, specifically:

[0112] 100g of chlorite mesoporous composite material C and 232g of 10% phosphotungstic acid aqueous solution were mixed and stirred at 40°C for 1h to completely dissolve; 17g of 15% bismuth trichloride aqueous solution was slowly added to the mixture; after the addition was completed, the mixture was stirred at 40°C for 5h. After the reaction was completed, stirring was stopped and the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 120°C for 3h and calcined at 300°C for 3h to obtain a new supported catalyst E.

[0113] Based on the total weight of the catalyst E, the content of the chlorite mesoporous composite material C was 80 weight %, and the content of bismuth phosphotungstate was 20 weight %.

[0114] The specific surface area of ​​catalyst E is 300m 2 / g, and the pore volume is 1.4ml / g.

[0115] The ketal reaction performance of catalyst E was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 94.2%.

[0116] Example 6

[0117] Catalyst F was prepared in the same manner as in Example 1, except that the preparation conditions of the novel supported catalyst in step (2) of Example 1 were changed, specifically:

[0118] 100g of chlorite mesoporous composite material A and 382g of 20% phosphotungstic acid aqueous solution were mixed and stirred at 60°C for 1h; 83g of 10% bismuth trichloride aqueous solution was slowly added to the mixture; after the addition was completed, the mixture was stirred at 60°C for 4h. The solvent water in the system was removed by a rotary evaporator, the solid product was dried at 100°C for 8h, and then calcined at 280°C for 4h to obtain a new supported catalyst F.

[0119] Based on the total weight of the catalyst F, the content of the chlorite mesoporous composite material A is 55 weight %, and the content of bismuth phosphotungstate is 45 weight %.

[0120] The specific surface area of ​​catalyst F is 113 m 2 / g, and the pore volume is 0.6ml / g.

[0121] The ketal reaction performance of catalyst F was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 93.3%.

[0122] Example 7

[0123] Catalyst G was prepared in the same manner as in Example 3, except that the preparation conditions of the novel supported catalyst in step (2) of Example 3 were changed, specifically:

[0124] 100g of chlorite mesoporous composite material C and 164g of 10% phosphotungstic acid aqueous solution were mixed and stirred at 40°C for 1h to completely dissolve; 12g of 15% bismuth trichloride aqueous solution was slowly added to the mixture; after the addition was completed, the mixture was stirred at 40°C for 5h. After the reaction was completed, stirring was stopped and the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 120°C for 3h and calcined at 300°C for 3h to obtain a new supported catalyst G.

[0125] Based on the total weight of the catalyst G, the content of the chlorite mesoporous composite material C was 85% by weight, and the content of bismuth phosphotungstate was 15% by weight.

[0126] The specific surface area of ​​catalyst G is 332 m 2 / g, and the pore volume is 1.5ml / g.

[0127] The ketal reaction performance of catalyst G was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 93%.

[0128] Comparative Example 1

[0129] Catalyst D1 was prepared in the same manner as in Example 1, except that the preparation conditions of the novel supported catalyst in step (2) of Example 1 were changed, specifically:

[0130] 100g of chlorite mesoporous composite material A and 1000g of 20% phosphotungstic acid aqueous solution were mixed and stirred at 60°C for 1h; 216g of 10% bismuth trichloride aqueous solution was slowly added to the mixture; after the addition was completed, the mixture was stirred at 60°C for 4h. The solvent water in the system was removed by a rotary evaporator, the solid product was dried at 100°C for 8h, and then calcined at 280°C for 4h to obtain a new supported catalyst D1.

[0131] Based on the total weight of the catalyst D1, the content of the chlorite mesoporous composite material A was 32% by weight, and the content of bismuth phosphotungstate was 68% by weight.

[0132] The specific surface area of ​​catalyst D1 is 82m 2 / g, and the pore volume is 0.3ml / g.

[0133] The ketal reaction performance of catalyst D1 was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 84.2%.

[0134] Comparative Example 2

[0135] Catalyst D2 was prepared in the same manner as in Example 3, except that the preparation conditions of the novel supported catalyst in step (2) of Example 3 were changed, specifically:

[0136] 100g of chlorite mesoporous composite material C and 59g of 10% phosphotungstic acid aqueous solution were mixed and stirred at 40°C for 1h to completely dissolve; 4g of 15% bismuth trichloride aqueous solution was slowly added to the mixture; after the addition was completed, the mixture was stirred at 40°C for 5h. After the reaction was completed, stirring was stopped and the solvent water was removed using a rotary evaporator to obtain a solid product. The solid product was dried at 120°C for 3h and calcined at 300°C for 3h to obtain a new supported catalyst D2.

[0137] Based on the total weight of the catalyst D2, the content of the chlorite mesoporous composite material C was 94 weight %, and the content of bismuth phosphotungstate was 6 weight %.

[0138] The specific surface area of ​​catalyst D2 is 343m 2 / g, and the pore volume is 1.6ml / g.

[0139] The ketal reaction performance of catalyst D2 was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 72.4%.

[0140] Comparative Example 3

[0141] Cancel step (1) in Example 1.

[0142] Catalyst D3 was prepared in the same manner as step (2) of Example 1, except that 100 g of the chlorite mesoporous composite material A was replaced with commercially available silica (purchased from Qingdao Hailang Silica Gel Desiccant Factory, with a specific surface area of ​​329 m 2 / g, pore volume is 0.6ml / g).

[0143] The specific surface area of ​​catalyst D3 is 195m 2 / g, and the pore volume is 0.3ml / g.

[0144] The ketal reaction performance of catalyst D3 was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 81%.

[0145] Comparative Example 4

[0146] Catalyst D4 was prepared in the same manner as in Example 1, except that "bismuth phosphotungstate" was replaced with "sodium phosphotungstate" to obtain catalyst D4 for synthesis. The specific steps are as follows:

[0147] The chlorite mesoporous composite material A was prepared in the same manner as step (1) in Example 1.

[0148] 100 g of chlorite mesoporous composite material A and 235 g of 20% sodium phosphotungstate aqueous solution were mixed and stirred at 60° C. for 5 h. The solvent water in the system was removed by a rotary evaporator, and the solid product was dried at 100° C. for 8 h, and then calcined at 280° C. for 4 h to obtain catalyst D4.

[0149] Based on the total weight of the catalyst D4, the content of the chlorite mesoporous composite material A was 68% by weight, and the content of the sodium phosphotungstate was 32% by weight.

[0150] The ketal reaction performance of catalyst D4 was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 83.7%.

[0151] Comparative Example 5

[0152] The chlorite mesoporous composite material A was prepared according to the method of step (1) in Example 1, and the ketal reaction performance was tested using the unloaded chlorite mesoporous composite material A as catalyst D5.

[0153] The ketal reaction performance of catalyst D5 was tested according to the method of step (3) in Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 1.3%.

[0154] Comparative Example 6

[0155] Catalyst D6 was prepared in the same manner as in Example 1, except that the preparation of the spherical chlorite mesoporous composite material in step (1) was omitted, and in step (2), "100 g of chlorite mesoporous composite material A" was replaced by "100 g of ZSM-5 molecular sieve carrier, and the specific surface area of ​​the replaced carrier was 356 m 2 / g, pore volume is 0.28ml / g, and the most probable pore diameter is 0.56nm".

[0156] The ketal reaction performance of catalyst D6 was tested according to the catalyst reaction performance evaluation method in step (3) of Example 1. The yield of 2,2-dimethyl-1,3-dioxolane was 74%.

[0157] It can be seen from the above results that the new supported catalyst provided by the present invention can catalyze the condensation reaction of acetone and ethylene glycol to produce 2,2-dimethyl-1,3-dioxolane, and obtain a higher yield of 2,2-dimethyl-1,3-dioxolane.

[0158] By comparing the data of Example 1 and Comparative Example 1, it can be seen that the contents of the carrier and bismuth phosphotungstate in Catalyst D1 are not within the range specifically defined by the present invention. When the content of the chlorite mesoporous composite material is too low and the content of the active component is too high, the active component is unevenly dispersed on the carrier, which will promote the formation of by-products and result in a low yield of 2,2-dimethyl-1,3-dioxolane.

[0159] By comparing the data of Example 1 and Comparative Example 2, it can be seen that the contents of the carrier and bismuth phosphotungstate in Catalyst D2 are not within the range specifically defined by the present invention. When the content of the chlorite mesoporous composite material is too high and the content of the active component is too low, the number of active centers is insufficient during the reaction and the catalyst efficiency is reduced, resulting in a lower yield of 2,2-dimethyl-1,3-dioxolane within the same reaction time.

[0160] By comparing the data of Example 1 and Comparative Example 3, it can be seen that if commercially available silica is used instead of the ultra-high specific surface area mesoporous carbon material carrier to prepare the esterification catalyst, since the pore volume of the commercially available silica carrier is relatively small and the pore shape and size are irregular, it is not conducive to the dispersion of the active components, which leads to a lower yield of 2,2-dimethyl-1,3-dioxolane.

[0161] Comparing the data of Example 1 and Comparative Example 4, it can be seen that the catalyst performance is significantly reduced when sodium phosphotungstate is used to replace bismuth phosphotungstate as the active component. This is because the catalytic activity of sodium phosphotungstate of the same weight is poor.

[0162] By comparing the data of Example 1 and Comparative Example 5, it can be seen that in Comparative Example 5, the unloaded chlorite mesoporous composite material is used as the condensation catalyst. Since the surface acidity of the chlorite mesoporous composite material is extremely weak, it cannot catalyze the ketal reaction, resulting in an extremely low yield of 2,2-dimethyl-1,3-dioxolane.

[0163] From the data of Comparative Example 1 and Comparative Example 6, it can be seen that in Comparative Example 6, the carrier is a ZSM-5 molecular sieve carrier. Since the ZSM-5 molecular sieve is a microporous material with a maximum pore diameter of 0.56 nm and a pore volume of 0.28 ml / g, the small pore volume is not conducive to the dispersion of the active component, resulting in an extremely low yield of 2,2-dimethyl-1,3-dioxolane.

[0164] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A novel supported catalyst, characterized in that: The novel supported catalyst comprises a chlorite mesoporous composite material and bismuth phosphotungstate supported on the chlorite mesoporous composite material; wherein the average particle size of the chlorite mesoporous composite material is 10-60 μm, and the specific surface area is 200-600 m 2 / g, the pore volume is 0.8-2mL / g, and the pore size is bimodal distribution; wherein the first most probable pore size and the second most probable pore size corresponding to the bimodal distribution are 3-6nm and 18-22nm, respectively; and based on the total weight of the catalyst, the content of the chlorite mesoporous composite material is 55-85% by weight, and the content of the bismuth phosphotungstate is 15-45% by weight.

2. The novel supported catalyst according to claim 1, wherein Based on the total weight of the catalyst, the content of the chlorite mesoporous composite material is 60-80% by weight, and the content of the bismuth phosphotungstate is 20-40% by weight; Preferably, based on the total weight of the catalyst, the content of the chlorite mesoporous composite material is 65-75% by weight, and the content of the bismuth phosphotungstate is 25-35% by weight.

3. The novel supported catalyst according to claim 1, wherein The specific surface area of ​​the chlorite mesoporous composite material is 228-349m 2 / g, the pore volume is 1.2-1.7 mL / g, and the first most probable pore diameter and the second most probable pore diameter are 3.6-4.2 nm and 19-21 nm, respectively.

4. The novel supported catalyst according to any one of claims 1 to 3, wherein The specific surface area of ​​the novel supported catalyst is 100-350m 2 / g, pore volume 0.6-1.5cm 3 / g; Preferably, the specific surface area of ​​the novel supported catalyst is 150-300m 2 / g, pore volume is 0.8-1.4cm 3 / g; More preferably, the specific surface area of ​​the novel supported catalyst is 180-270 m 2 / g, pore volume is 1-1.3cm 3 / g.

5. A method for preparing a novel supported catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The bismuth trichloride solution is added dropwise to a mixed solution of a chlorite mesoporous composite material and a phosphotungstic acid solution to react, and the solvent after the reaction is removed to obtain a solid product; the solid product is dried and calcined to obtain a novel supported catalyst.

6. The preparation method according to claim 5, wherein: The concentration of the bismuth trichloride solution is 1-30% by weight; and / or, the concentration of the phosphotungstic acid solution is 2-50 wt %; And / or, the weight ratio of the chlorite mesoporous composite material, the phosphotungstic acid solution and the bismuth trichloride solution is 1:(1-8):(0.1-2), preferably 1:(1.5-4):(0.1-1.2).

7. The preparation method according to claim 5, wherein: The reaction conditions include: reaction temperature of 10-80°C, preferably 20-60°C; reaction time of 1-30h, preferably 3-8h; And / or, the calcination conditions include: a calcination temperature of 200-400° C., preferably 250-300° C.; and a calcination time of 1-10 h, preferably 3-6 h.

8. A method for preparing 2,2-dimethyl-1,3-dioxolane, characterized in that: The method comprises: contacting acetone with ethylene glycol in the presence of a catalyst and a water-carrying agent to carry out a condensation reaction, wherein the catalyst is the novel supported catalyst according to any one of claims 1 to 3.

9. The method according to claim 8, wherein: The water-carrying agent is cyclohexane or benzene; And / or, the weight ratio of the novel supported catalyst, the water-carrying agent, acetone and ethylene glycol is 1:(8-50):(10-60):(20-100).

10. The method according to claim 8, wherein: The conditions of the condensation reaction include: temperature of 60-100° C. and time of 0.5-10 h.

Citation Information

Patent Citations

  • Chlorite mesoporous composite material, supported catalyst, preparation method thereof, application and preparation method of cyclohexanone glycerol ketal

    CN105149011A

  • Illite mesoporous composite material, supported catalyst and preparation method and application thereof and preparation method of cyclohexanone glyceryl ketal

    CN105435850A

  • Isobutane dehydrogenation catalyst using chlorite composite material with three-dimensional cubic and hexagonal pore channel structures as carrier, preparation method and applications thereof

    CN110732342A

  • Catalyst for synthesizing methyl methacrylate as well as preparation method and application of catalyst

    CN115608406A

  • Catalyst for Producing Acrylic Acids and Acrylates

    US20130245311A1

Cited By

  • Bismuth phosphotungstate as well as preparation method and application thereof

    CN120463239A